Mental health status and its correlates among people living with HIV/AIDS in a tertiary care center of West Bengal - Islam, Shahinoor; Das, Sulagna; Naga, Dinobandhu; Taraphdar, Pranita (International Journal of Research in Medical Sciences, 2023)
Background: People with mental disorders experience disproportionately higher rates of disability and mortality. Bidirectional link between mental illness and HIV/AIDS accelerates the disease progression, reduces willingness to access health care, promotes high risk behavior, leads to low medication adherence, and ultimately results in poor disease outcome. The present study was conducted with the objectives to estimate the prevalence of common mental disorders (CMD) among people living with HIV/AIDS (PLWHA) attending anti-retroviral therapy (ART) clinic at Burdwan medical college and hospital and to find out the association if any, between sociodemographic characteristics and CMD among the study population. Methods: A cross sectional descriptive study was conducted among 410 adult PLWHA, selected through systematic random sampling, registered at ART clinic of Burdwan medical college and hospital, West Bengal during October 2022 to February 2023. Interview of each study subject, with a pre-designed, pre-tested, semi-structured schedule was done to obtain socio-demographic characteristics and CMD was assessed using WHO’s self-reporting questionnaire (SRQ)-20. Univariate and multivariable logistic regression was performed to predict the factors associated with CMD. Data were analysed using SPSS v23. Results: Prevalence of CMD was 30.2% among PLWHA attending ART clinic. In univariate logistic regression, female gender, persons not living with partner (un-married, widow/widower, divorced/separated), current smoker, pre-ART cases and persons with WHO stage 3 disease were found to be significantly associated with presence of CMD. But in multivariable logistic regression, persons not living with partner [AOR 2.114 (95% CI: 1.228-3.641)] and pre-ART cases [AOR 8.909 (95% CI: 4.770-16.640)] were remained statistically significant. Conclusions: Screening and treating the PLWHA suffering from CMD, should be considered to be an integral part of HIV care, support and treatment at the primary level.